Violence and Persons with Disabilities: Abusing as Destiny - Renata Martinec (Društvene i Humanističke Studije)
People with disabilities are “easy targets” because they often lack the acquired knowledge of appropriate or unacceptable behaviour, do not have sufficient acquired social skills, or sometimes believe that because of their disorders and dependence on others, they must be conciliatory and have no right to protest or rebel. Also, a physical or psychological deviation that sometimes suggests a person’s weakness in others can cause a sense of dominance and superiority, which in certain situations can turn into the intention of physical or emotional abuse. Unfortunately, statistics show that a greater number of people with disabilities have faced some types of violence to a greater or lesser extent, especially in the female population. Violence can have numerous and psychophysical severe consequences on people who are already struggling with health, functional and/or mental disorders and consequently have difficulties in realizing the required quality of life and human rights. For this reason, the task of the entire society should be aimed at preventing a spiral mechanism in which one fateful unfavourable situation, such as disability, triggers a series of others. Regardless of its potential, every being deserves care and protection, especially vulnerable groups whose suffering, pain or limitations are seen as their inevitable destiny. However, the strength, fighting spirit and dedication shown by people with disabilities are proof of their magnificence, which should not be rewarded with verbal or physical blows, but with tolerance, respect, and appreciation.